Hydrogel-based strategies to advance therapies for chronic skin wounds - da Silva, L. P. (2019)
Chronic skin wounds are the leading cause of nontraumatic foot amputations worldwide and present a significant risk of morbidity and mortality due to the lack of efficient therapies.The intrinsic characteristics of hydrogels allow them to benefit cutaneous healing essentially by supporting a moist environment. This property has long been explored in wound management to aid in autolytic debridement. However, chronic wounds require additional therapeutic features that can be provided by a combination of hydrogels with biochemical mediators or cells, promoting faster and better healing.We survey hydrogel-based approaches with potential to improve the healing of chronic wounds by reviewing their effects as observed in preclinical models. Topics covered include strategies to ablate infection and resolve inflammation, the delivery of bioactive agents to accelerate healing, and tissue engineering approaches for skin regeneration. The article concludes by considering the relevance of treating chronic skin wounds using hydrogel-based strategies.